1998
DOI: 10.1093/humupd/4.3.301
|View full text |Cite
|
Sign up to set email alerts
|

Impact of heavy metals on hormonal and immunological factors in women with repeated miscarriages

Abstract: In 111 women with repeated miscarriages, the urinary excretion of heavy metals was determined in a challenge test with the chelating agent 2,3-dimercaptopropane-1-sulphonic acid in addition to hormonal, chromosomal, immunological and uterine investigations. The heavy metal excretion was correlated to different immunological (natural killer cells, T cell subpopulations) and hormonal (progesterone, oestradiol, prolactin, thyroid stimulating hormone) parameters. We conclude that heavy metals seem to have a negati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
39
0
1

Year Published

1999
1999
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 79 publications
(47 citation statements)
references
References 36 publications
7
39
0
1
Order By: Relevance
“…A Korean study of manganese exposure reported higher levels of FSH and LH among male welders compared to age-matched office workers (27). Mercury, a transition metal and common environmental contaminant, was recently found to be associated with increased estradiol levels in both males and females from a small residential population in Cambodia (28), which was in agreement with a previous study among women with repeated miscarriages (29). However, slight to no relationships were reported in earlier studies of occupational exposure to mercury and hormone levels (3032).…”
Section: Introductionsupporting
confidence: 90%
“…A Korean study of manganese exposure reported higher levels of FSH and LH among male welders compared to age-matched office workers (27). Mercury, a transition metal and common environmental contaminant, was recently found to be associated with increased estradiol levels in both males and females from a small residential population in Cambodia (28), which was in agreement with a previous study among women with repeated miscarriages (29). However, slight to no relationships were reported in earlier studies of occupational exposure to mercury and hormone levels (3032).…”
Section: Introductionsupporting
confidence: 90%
“…Our findings that suggest a positive association between progesterone and lead differ from those of studies of higher levels of lead exposure in monkeys that showed inverse associations with progesterone (Foster et al 1996; Laughlin et al 1987). A cross-sectional study of women with repeated miscarriage reported that follicular-phase estradiol was positively associated with mercury and lead (Gerhard et al 1998), and our findings were similar for lead, although not statistically significant. Our study suggests that environmental exposures to metals may be associated with modest hormonal effects in healthy, regularly menstruating women, a population not often assessed in relation to environmental or hormonal outcomes.…”
Section: Discussionsupporting
confidence: 72%
“…On the other hand, a proportion of the spontaneous abortions in the embryologic period can be explained by foetal chromosomal aberrations and aneuploidy (Eiben et al 1990). An exposure may increase the risk of spontaneous abortion in a specific period of pregnancy as each may have different risks (Modvig et al 1990) and mechanisms (Gerhard et al 1998). Modvig et al concluded that a study design appropriate for measuring the total risk of spontaneous abortion from conception to the 28th week did not exist.…”
Section: Discussionmentioning
confidence: 99%